PENGARUH LATIHAN MULTIBALL TERHADAP KEMAMPUAN FOREHAND DRIVE ATLET TENIS MEJA DI CLUB PIMPONG ACEH BESAR - syahrianursaifi; Zulheri Is (Journal of Health and Recreation Physical Education (JHRPE), 2026)
This study aims to determine the effect of multiball training on the forehand drive ability of table tennis athletes at Club Pimpong Aceh Besar. The study uses a quantitative approach with a quasi-experimental method through a one-group pretest–posttest design. The research sample consists of 8 table tennis athletes selected using a total sampling technique. The research instrument is a forehand drive ability test administered before and after the multiball training treatment. Descriptive analysis results show that the mean score of athletes’ forehand drive ability in the pretest is 36.75 with a standard deviation of 5.63, while in the posttest it increases to 46.50 with a standard deviation of 6.59. The normality test using the Shapiro–Wilk test shows that the pretest data have a significance value of 1.000 (> 0.05) and the posttest data have a significance value of 0.995 (> 0.05), indicating that the data are normally distributed. Hypothesis testing using the paired t-test shows a calculated t value of 19.44 with 7 degrees of freedom (df) and a significance value (p-value) of 0.000 (< 0.05). Based on these results, it can be concluded that multiball training has a significant effect on improving the forehand drive ability of table tennis athletes at Club Pimpong Aceh Besar. Multiball training can be used as an effective training method in developing basic table tennis techniques at the club level